The Graduate Profile Learning Outcomes Cyclical Integration Model (MIS-PC): Reconstructing the Higher Education Curriculum Development Framework - Yoga Mahath Pandika; Dilla Muckti Jihansyah; Ilham Ainur Roziqin; Imam Junaris (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2026)
Higher education curriculum development requires a clear, systematic formulation of graduate profiles and Graduate Learning Outcomes (Capaian Pembelajaran Lulusan/CPL) that responds to societal and labor-market needs. Existing formulations, however, tend to present the stages of developing graduate profiles and CPL as a linear, fragmented sequence, a practice that contributes to persistent misalignment between graduate profiles, learning outcomes, and curriculum structure. This study reconstructs the five-stage formulation process commonly found in the literature into an integrated cyclical framework, termed the Graduate Profile Learning Outcomes Cyclical Integration Model (MIS-PC). Using a qualitative library research design, data were drawn from 24 academic sources comprising peer-reviewed journal articles, scholarly books, and higher-education policy documents on curriculum development and Outcome-Based Education (OBE) selected from an initial pool of 68 sources identified through Google Scholar, Scopus, and Sinta. Data were analyzed descriptively through data reduction, data display, and conclusion drawing. The findings show that the conventional linear representation obscures feedback relationships that, in practice, link stakeholder-needs analysis, graduate-profile formulation, CPL development, alignment with higher-education standards, and curriculum integration. Treating these five stages as a closed feedback cycle, mediated by a single integrated mapping instrument, offers a more efficient and accurate pathway for curriculum teams to reach coherent outcomes. The MIS-PC model is proposed as a practical alternative that reduces redundant documentation while strengthening alignment between graduate profiles, CPL, and curriculum structure; as a conceptual, library-based contribution, however, the model has not yet been empirically tested and should be treated as a proposition for further validation rather than a proven intervention